PREFERENTIAL STAINING OF NUCLEIC ACID-CONTAINING STRUCTURES FOR ELECTRON MICROSCOPY - Huxley, H. E. (The Rockefeller University Press, 1961)
Oriented fibres of extracted nucleohistone were employed as test material in a study of satisfactory fixation, embedding, and staining methods for structures containing a high proportion of nucleic acid. Fixation in buffered osmium tetroxide solution at pH 6, containing 10(-2) M Ca(++), and embedding in Araldite enabled sections of the fibres to be cut in which the orientation was well preserved. These could be strongly stained in 2 per cent aqueous uranyl acetate, and showed considerable fine structure. Certain regions in the nuclei of whole thymus tissue could also be strongly stained by the same procedure, and were identical with the regions stained by the Feulgen procedure in adjacent sections. Moreover, purified DNA was found to take up almost its own dry weight of uranyl acetate from 2 per cent aqueous solution. Strongest staining of whole tissue was obtained with very short fixation times-5 minutes or so at 0°C. Particularly intense staining was obtained when such tissue stained in uranyl acetate was further stained with lead hydroxide. Although the patterns of staining by lead hydroxide alone and by uranyl acetate were similar in tissues fixed for longer times (½ hour to 2 hours, at 0°C or 20°C), in briefly fixed material the DNA-containing regions appeared relatively unstained by lead hydroxide alone, whilst often there was appreciable staining of RNA-containing structures. Observations on the staining of some viruses by similar techniques are also described.